# Question 9.19: Use the inverse matrix to solve the following simultaneous e......

Use the inverse matrix to solve the following simultaneous equations:

x − 2z = 4
2x + 2y + 3z = 15
x + 3y + 2z = 12

Step-by-Step
The 'Blue Check Mark' means that this solution was answered by an expert.

Step 1: Write all the equations in the same order: variables (in order) = RHS. Write down the matrices A and B. Thematrix A is the matrix of coefficients of the three equations, all arranged in the same format; B is the column matrix consisting of the constants from the RHS of the equations.

A = $\left(\begin{matrix} 1 & 0 & -2 \\ 2 & 2 & 3 \\ 1 & 3 & 2 \end{matrix} \right)$        B = $\left(\begin{matrix} 4 \\ 15\\ 12 \end{matrix} \right)$

Step 2: Since X = $A^{−1}$ B, determine the inverse of A. However, if you look carefully at A, you will see that this matrix is identical to the matrix D in Worked Examples 9.17 and 9.18 in which the inverse of D was determined; therefore

$A^{−1} =\frac{1}{-13} \left(\begin{matrix} -5 & -6 & 4 \\ -1 & 4 & -7 \\ 4 & -3 & 2 \end{matrix} \right)$

So proceed straight away to the next step.

Step 3: Premultiply the matrix B by the inverse of A:

$X = A^{−1} B$

$\left(\begin{matrix} x \\ y\\ z \end{matrix} \right) =\frac{1}{-13} \left(\begin{matrix} -5 & -6 & 4 \\ -1 & 4 & -7 \\ 4 & -3 & 2 \end{matrix} \right) \left(\begin{matrix} 4 \\ 15\\ 12 \end{matrix}\right) = -\frac{1}{13} \left(\begin{matrix} -62 \\ -28\\ -5 \end{matrix}\right) = \left(\begin{matrix} 4.77 \\ 2.15\\ 0.38 \end{matrix}\right)$

$\left(\begin{matrix} x \\ y\\ z \end{matrix} \right) = \left(\begin{matrix} 4.77 \\ 2.15\\ 0.38 \end{matrix}\right)$

The solutions may simply be read off (correct to two decimal places), x = 4.77,
y = 2.15, z = 0.38.

Question: 9.7

## Solve the following equations by Gaussian elimination: x + y − z = 3 (1) 2x + y − z = 4 (2) 2x + 2y + z = 12 (3) ...

All three equations must be written in the same fo...
Question: 9.20

## Given the input/output table for the three-sector economy: ...

Step 1: Use the underlying assumption total input=...
Question: 9.18

## (a) Find the inverse of the matrix D = (1 0 -2 2 2 3 1 3 2) (b) Show that DD^0−1 = I. ...

(a) Use the definition of the inverse given in equ...
Question: 9.17

## (a) Find the inverse of the matrix D = ( 1 0 -2 2 2 3 1 3 2) by Gauss–Jordan elimination. (b) Show that DD^–1 = I. ...

(a) Write out the augmented matrix consisting of t...
Question: 9.12

## Given the supply and demand functions for two related goods, A and B,Good A :{Qda = 30 − 8Pa + 2Pb {Qsa = −15 + 7Pa Good B :{Qdb = 28 + 4Pa − 6Pb {Qsb = 12 + 2Pb (a) Write down the equilibrium condition for each good. Hence, deduce two equations in Pa and Pb . (b) Use Cramer’s rule to find the ...

(a) The equilibrium condition for each good is tha...
Question: 9.9

## Solve the following equations by Gauss–Jordan elimination: 2x + y + z = 12 6x + 5y − 3z = 6 4x − y + 3z = 5 ...

Rearrange the equations to have variables on the L...
Question: 9.8

## Solve the following equations by Gaussian elimination: 2x + y + z = 12 6x + 5y − 3z = 6 4x − y + 3z = 5 ...

The equations are already written in the required ...
Question: 9.2

## A company manufactures two types of wrought iron gates. The number of labour-hours required to produce each type of gate, along with the maximum number of hours available, are given in Table 9.3. ...

(a) For x type I gates and y type II gates, the nu...
Question: 9.21